2002
DOI: 10.4049/jimmunol.168.1.400
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Rho-p160 Rho Coiled-Coil Kinase Axis in the Chemokine Stromal Cell-Derived Factor-1α-Induced Lymphocyte Actomyosin and Microtubular Organization and Chemotaxis

Abstract: The possible involvement of the Rho-p160ROCK (Rho coiled-coil kinase) pathway in the signaling induced by the chemokine Stromal cell-derived factor (SDF)-1α has been studied in human PBL. SDF-1α induced activation of RhoA, but not that of Rac. RhoA activation was followed by p160ROCK activation mediated by RhoA, which led to myosin light chain (MLC) phosphorylation, which was dependent on RhoA and p160ROCK activities. The kinetics of MLC activation was similar to that of RhoA and p160ROCK. The role of this cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
79
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 55 publications
14
79
0
Order By: Relevance
“…Downstream effectors of RhoA involved in actin reorganization and cell migration include the kinase p160ROCK and mDia, but the roles of these effectors in lymphoid motility have been assessed only in the former (20,21). Here, it is demonstrated that mDia was present in very small amounts in freshly isolated PBL, but was induced both in vivo and in vitro during T cell activation.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Downstream effectors of RhoA involved in actin reorganization and cell migration include the kinase p160ROCK and mDia, but the roles of these effectors in lymphoid motility have been assessed only in the former (20,21). Here, it is demonstrated that mDia was present in very small amounts in freshly isolated PBL, but was induced both in vivo and in vitro during T cell activation.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, exposure of lymphoid cells to chemokines induces a robust, but transient, increase in the cellular F-actin pool (42). Chemokines such as SDF-1␣ activate Cdc42 (43) and RhoA (20), and a detailed kinetics study of these two GTPases revealed that Cdc42 activation occurs earlier than RhoA. Furthermore, inhibition of RhoA by the ADP-ribosyltransferase C3 did not impair the increase in F-actin elicited by chemokines (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them (e.g., CCR5 and CXCR4) participate in HIV infection of CD4 ϩ T lymphocytes as coreceptors (Berger et al, 1999). Ligand binding to the chemokine receptors triggers various signaling cascades, including activation of G proteins, phosphotidylinositol 3-kinase, Janus kinase/signal transducers and activators of transcription proteins, the Rho-p160 ROCK axis, and the MAPK pathway (Wu et al, 1993;Ganju et al, 1998;Mellado et al, 1998;Vicente-Manzanares et al, 1999;Vicente-Manzanares et al, 2002). Chemokine activation of these intracellular signals is often accompanied by chemokine receptor internalization and trafficking back to the cell membrane.…”
mentioning
confidence: 99%